Gaming Concepts for Tackling Societal Challenges: A Preliminary Survey and Analysis - Jaser, Edward; Doofesh, Yazan; Mihalachi, Luminita (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Governments, and to a certain extent non-governmental organizations, around the world have to continuously deal with complex and dynamic societal challenges. One approach that has gained increasing popularity over the last two decades is the use of Information and Communication Technologies (ICT) as a tool to enhance impact and deliver efficiency and effectiveness. Therefore, we have been witnessing wide spectrum of ICT interventions to address and inhibit challenging and complex societal problems. One area of ICT that has been attracting more attention recently is the use of games and gaming concepts for this purpose. In this paper, we provide analysis about major societal challenges that are shared internationally and analyse video games that are designed to address these challenges